KAJIAN SOSIAL EKONOMI PENGRAJIN GULA AREN DI DESA KALAIT DUA KECAMATAN TOULUAAN SELATAN KABUPATEN MINAHASA TENGGARA - Monalika Nainggolan; Hermon Maurits Karwur; Kalvin Salindeho Andaria (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2020)
The problems in this study are the declining condition of the plantations and palm plants, the uncertain income of the palm sugar craftsmen, the large number, the low educational background, the number of dependents that have to be financed by the head of the family and the government who is less active in supporting the economic activities of the craftsmen in Indonesia. Kalait Dua Village, South Toulongga District, Southeast Minahasa Regency. The purpose of this study was to examine the socio-economic life of palm sugar craftsmen in Kalait Dua Village, South Toulua District, Southeast Minahasa Regency. The research method used is descriptive qualitative. The data collection techniques used were direct observation, interviews, documentation and FGD (Focused Group Discussion). The informants in this study were 5 palm sugar craftsmen. The data analysis technique used was the Milles and Huberman technique, namely data reduction, data presentation and conclusion drawing. The results showed, 1) The condition of the palm tree plantations in Kalait Dua Village, South Touluing District, Southeast Minahasa Regency was classified both in its existence and productivity. 2) The income condition is classified as high, namely 2,000,000 to 4,000,000 per month. 3) The level of education is low. 4) The level of responsibility of the head of the family is relatively low. 5) The role of the government has not been classified as good enough.